Endurance training promotes the browning of WAT by enhancing the NPFF pathway in the hypothalamus in rats with type 2 diabetes - Syiedeh Maryam Mousavi; Fatemeh Zahra Gorji; Ziya Fallahmohammadi; Khadijeh Nasiri; Abolfazl Akbari (Iranian Journal of Basic Medical Sciences, 2025)
Objective(s): Type 2 diabetes (T2D) represents a complex and multifactorial disorder, and efforts to discover its treatment are necessary. Browning of white adipose tissue (WAT) as a therapeutic target for diabetes seems to be induced by exercise through neuropeptide FF (NPFF) signaling in the hypothalamus and adipose tissue. This study aimed to explore the role of endurance training on the browning of WAT by assessing the expression of the gene and protein of NPFF and its receptors in the hypothalamus and adipose tissue.Materials and Methods: Forty adult male Wistar rats were assigned into four groups: control, exercise, diabetic control, and diabetic exercise. The serum levels of lipid profile, insulin, and glucose, along with the expression of gene and protein of NPFF and its receptors (NPFFR1 and NPFFR2), were evaluated in the hypothalamus and adipose tissue. A histological examination was performed to evaluate the browning of WAT.Results: Metabolic parameters notably increased in the diabetic group. The gene and protein expression of NPFF and its receptors significantly decreased in the hypothalamus and fat tissue in the diabetic group. However, these changes in the hypothalamus, not in the adipose tissue, were significantly improved in the diabetic-exercise group compared to the diabetic group. The high WAT content in diabetic rats was decreased by exercise, leading to an increase in the browning of WAT.Conclusion: Endurance progressive training could centrally, not peripherally, promote the browning of WAT in diabetic rats by enhancing the expression of gene and protein of NPFF and its receptors in the hypothalamus.